Epidemiology Of Measles And Its Complications In Non- Hospitalized Children - Mangal N; Shah K; Sitaraman S; Gupta S D (Wolters Kluwer Medknow Publications, 1990)
This study was conducted in 1985-86 amongst non-hospitalized children of jaipur city in33 investigative units having 3791 families with 6183 children in the 0-9 years age group. Measles vaccine coverage was only 21.7% Measles developed in 189 cases. Maximum incidence occurred in the 1-2 years olds and during the first half of the years (January to June). Complication developed in 50 (26.5%) children. The most frequent was diarrohea (14.3%) followed by respiratory infection (6.9%). No case fatality was reported.